40S ribosomal protein S18 is a novel maternal peptidoglycan-binding protein that protects embryos of zebrafish from bacterial infections. (December 2021) - Wang, Xia; Ren, Yiqing; Gong, Chengming; Chen, Yufei; Ge, Xiaoping; Kong, Jun; Sun, Wenjing; Du, Xiaoyuan
Abstract: Previous studies have shown that ribosomal proteins play important roles in ribosome assembly and protein translation, but other biological functions remain ill-defined. Here it is clearly demonstrated that RPS18 is a newly identified PGN-binding protein which is present abundantly in the eggs/embryos of zebrafish. Recombinant RPS18 not only identifies the bacterial signature molecule PGN, LPS, and LTA, and binds the bacteria as a pattern recognition receptor, but also kills the Gram-positive and Gram-negative bacteria as an antibacterial effector molecule. What is important is that, we reveal that microinjection of rRPS18 into early embryos significantly improved the resistance of the embryos against pathogenic Aeromonas hydrophila challenge, and co-injection of anti-RPS18 antibody could markedly reduced this improved bacterial resistance. In summary, these results indicate that RPS18 is a maternal immune factor that can protect the early embryos of zebrafish against pathogenic attacks. This work also provides another angle for understanding the biological functions of ribosomal proteins. Highlights: 40S ribosomal protein S18 (RPS18) is a newly identified PGN-binding protein present abundantly in the eggs/embryos of zebrafish. Recombinant RPS18 acts as a pattern recognition receptor and functions as an antibacterial effector molecule directly killing the bacteria. RPS18 can protect the early embryos of zebrafish against bacterial infections.